The Concept Of Implied License To Use: Is There Room For Equitable Estoppel By Conduct? - Abd. Ghani Azmi, Idn Madleha (Journal of Malaysian and Comparative Law, 1999)
Parallel imports occur when non-authentic - not counterfieted - products are imported cheaply without the consent of the authorised dealer or licensee in a particular jurisdiction.